Structural isomers of 9-(pyridin-2-yl)-9H-carbazole in combination with 9′H-9, 3':6′, 9″-tercarbazole and their application to high efficiency solution processed green TADF OLEDs. (August 2020) - Hwang, Jinhyo; Yoon, Jiwon; Kim, Chae Yeong; Choi, Suna; Kang, Hyunchul; Kim, Jun Yun; Yoon, Dae-Wi; Han, Chang Wook; Park, Sungnam; Cho, Min Ju; Choi, Dong Hoon
Abstract: Two host materials, CzPy2TCz and CzPy3TCz, were designed as structural isomers and synthesized to achieve high efficiency thermally activated delayed fluorescence-organic light emitting diodes (TADF-OLEDs). The design strategy involved introducing a pyridine group into the core structure as an electron-withdrawing unit and varying the substitution position of tercarbazole (TCz) . To realize green TADF-OLED, the two host materials synthesized in this study have excellent thermal stability and high excited triplet energy (T1 = 2.95–2.98 eV). The maximum external quantum efficiency and current efficiency values for CzPy2TCz were 23.81% and 80.2 cd/A, respectively and the respective values for CzPy3TCz were 20.27% and 70.1 cd/A, respectively. Structural isomers with carbazole (Cz) and TCz units at the 2, 6-position of the pyridine core effectuate better device performance. Consequently, we found that the host materials introduced in this study play an important role in implementing high performing solution-processed green TADF-OLED. Graphical abstract: Image 1 Highlights: Structural isomeric host materials, CzPy2TCz and CzPy3TCz were successfully synthesized. CzPy2TCz and CzPy3TCz achieved high triplet energy of 2.95 and 2.98 eV, respectively. Host:dopant blend films showed high morphological stability after thermal annealing. Corresponding green TADF-OLED by solution process exhibited high EQE over 20%.